Decadal variability of eddy temperature fluxes in the Labrador Sea. (April 2023) - Danek, Christopher; Scholz, Patrick; Lohmann, Gerrit
Abstract: Small-scale eddies play an important role in preconditioning and restratifying the water column before and after mixing events, thereby affecting deep water formation variability. Results from a realistic eddy-resolving ( ∼ 5 km local horizontal resolution) ocean model suggest that small-scale temperature fluxes due to turbulent potential to kinetic energy conversion are the main driver of mixed layer restratification during deep convection in the Labrador Sea interior and the West Greenland Current. This resupply of heat due to turbulent upward buoyancy fluxes exhibits a large interannual variability imposed by the atmospheric forcing. Eddy fluxes only become active in periods of strong buoyancy loss, while being quiescent otherwise. In a low-resolution ( ∼ 20 km) control simulation the modeled turbulence is strongly reduced and the associated modeled and parameterized heat fluxes are too weak to increase stratification. Highlights: High-resolution (5 km) temperature fluxes restratify Labrador Sea mixed layer. Large interannual variability of baroclinic instabilities and eddy buoyancy fluxes. Modeled and parameterized fluxes are too weak to increase stratification at 20 km.